Fenomena Praktik Sharenting sebagai Presentasi Orang Tua di Media Digital (Studi Netnografi pada akun Instagram @mas_natsuki dan @sana.arra_) - Faradila, Nindi; Asri, Rahman (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study explores the phenomenon of sharenting as a form of parental self-presentation on social media, particularly Instagram. Utilizing a qualitative approach with a netnographic method, this research analyzes two Instagram accounts, @mas_natsuki and @sana.arra_, to understand how parents share their children's lives and how public responses are formed, which can encompass various aspects related to interactions and participation from users commenting on the posts made on the accounts @mas_natsuki and @sana.arra_. The findings of this study reveal that the practice of sharing content can have both positive and negative impacts, depending on how and in what context the content is shared. The account @mas_natsuki demonstrates an educational, privacy-conscious, and inspirational approach, while @sana.arra_ reflects a more controversial form of sharenting that leads to online bullying. Based on the results of this research, it is recommended that parents cultivate ethical awareness and digital literacy when sharing content related to their children online, in order to balance self-expression, education, and child protection.